(untitled) (International Journal of Nursing Education, 2019)
Nameless nursing informaticians have been part of the tech-culture for more than two decades imbibing it like a sponge and have muddled through the successful and not so successful initiatives in healthcare. With the changing times and recognition of efforts that nurses continue to put in digital patient care, universally nursing informatics has grown as a separate field. In India, Health Information Technology (HIT) has made the nursing fraternity to adopt digital healthcare, however the extent of percolation remains questionable until we measure it as objectively as possible. The only way to do so is educate and check the skill competencies of nursing students and practicing nursing professional including researchers, educators, administrators and clinical nurses. The article explores the nursing informatics curriculum taught to student nurses in India. The basic and advance competencies in computer application, information literacy and management have been proposed for nursing students and nursing professionals in Indian setting